2017
DOI: 10.1530/edm-17-0093
|View full text |Cite
|
Sign up to set email alerts
|

Sensor-augmented CSII therapy with predictive low-glucose suspend following total pancreatectomy

Abstract: Pancreatogenic diabetes is characterised by recurrent severe hypoglycaemia due to changes in both endocrine and exocrine functions. There are no guidelines to manage these individuals. Herein, we describe the post-operative management of two people who developed pancreatogenic diabetes following total pancreatectomy for neuroendocrine malignancy. In both individuals, diabetes was managed using sensor-augmented predictive low-glucose suspend continuous subcutaneous insulin infusion (CSII). We demonstrate the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
7
1
1
Order By: Relevance
“…21,22 High rates of hypoglycemia were observed in previous studies in patients with diabetes following pancreatic resection. [27][28][29] Although the frequency of hypoglycemic episodes was higher in the FCPD group, we did not observe significant differences in hypoglycemic indices between the two groups. This discordance could be attributed to three factors: (a) relative preservation of endocrine and exocrine function and counterregulatory responses in FCPD compared to that following total pancreatectomy.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…21,22 High rates of hypoglycemia were observed in previous studies in patients with diabetes following pancreatic resection. [27][28][29] Although the frequency of hypoglycemic episodes was higher in the FCPD group, we did not observe significant differences in hypoglycemic indices between the two groups. This discordance could be attributed to three factors: (a) relative preservation of endocrine and exocrine function and counterregulatory responses in FCPD compared to that following total pancreatectomy.…”
Section: Discussioncontrasting
confidence: 73%
“…41 In another study, predictive low-glucose suspend using CGM and sensor-augmented continuous subcutaneous insulin infusion improved glycemic control and reduced hypoglycemia in patients with pancreatogenic diabetes following total pancreatectomy. 28 CGM using artificial endocrine pancreas during perioperative period improved glycemic control and reduced hypoglycemia in pancreatogenic diabetes after pancreatic resection. 42 The limitations of this study include application of CGM during hospitalization, which might differ from that of ambulatory home values.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Patienten/-innen mit CFRD und MODY, die eine Insulintherapie benötigen, werden diese Hilfsmittel im Vergleich zu Patienten/-innen mit Diabetes Typ 1 weniger häufig genutzt. Bei Patienten/-innen mit pankreoprivem Diabetes sind Insulinpumpe und CGM ebenfalls nur selten Bestandteil der Therapie, obwohl bei dieser Gruppe auch Störungen der Gegenregulation mit ausgeprägten Hypoglykämien zu erwarten sind [48,49]. Von den Patienten/-innen mit Diabetes Typ 2 und Insulintherapie ist trotz positiver Studienergebnisse [8,50] bisher unter 1 % mit diesen Hilfsmitteln versorgt.…”
Section: Diskussionunclassified
“…In recent years, growing evidences suggest that CSII also shows superiority over MDI during the perioperative period in patients with type 2 diabetes or pancreatogenic diabetes . This aroused great interest in developing a proper protocol for CSII use during surgery …”
Section: Introductionmentioning
confidence: 99%
“…26 This aroused great interest in developing a proper protocol for CSII use during surgery. [27][28][29][30] Our previous study showed that CSII improved hyperglycemia in perioperative patients. 31 However, it is important to investigate whether improvement of hyperglycemia leads to reduction of surgery-related complications in perioperative patients.…”
mentioning
confidence: 98%